Conocemos las áreas naturales protegidas de nuestra región y los beneficios que nos brindan - Alva Malca de Mendoza, Maritza del Pilar (2019)
The learning session entitled “Conocemos las áreas naturales protegidas de nuestra región y los beneficios que nos brindan” (Identifying the protected natural areas in our region and the benefits they offer us) has been planned for making primary school learners reflect on and analyze the importance these areas have for the biodiversity conservation, for promoting tourism which provides jobs to lots of people, for building citizenship and saving natural and cultural heritage as well as for fostering research and environmental education. This learning session is aimed to develop the personal and social skills of the forth- grade school boys and girls of “Juan Velasco Alvarado” school in Trujillo city, La Libertad región in Peru, regarding their competence to manage the site and the environment responsibly It has been planned involving both the pedagogical processes related to a learning sesión and the didactic processes corresponding to the personal and social learning area. An active methodology was developed as long as the learners participated constantly and enthusiastically during the whole session. A checklist was used as an asessment intrument.